Sports media transformation, integration, consumption - Billings, Andrew C. (Electronic media research series., 2011)
"Looking toward a future with increasingly hybridized media offerings, Sports Media: Transformation, Integration, Consumption examines sports media scholarship and its role in facilitating understanding of the increasingly complex world of sports media. Acknowledging that consumer demand for sports media content has influenced nearly every major technology innovation of the past several decades, chapters included herein assess existing scholarship while positing important future questions about the role sports media will play in the daily lives of sports fans worldwide. Contributions from well-known scholars are supplemented by work from younger researchers doing new work in this area. Developed for the Broadcast Education Association's Electronic Media Research series, this volume will be required reading for graduate and undergraduate students in media, communication, sociology, marketing, and sports management, and will serve as a valuable reference for future research in sports media"--